Gene Polymorphisms Increasing the Risk of Intracranial Aneurysms: Interleukin-1β -511C>T (Part I) - Giotta Lucifero , Alice; Baldoncini, Matias; Foiadelli, Thomas; Brambilla, Ilaria; Savioli, Gabriele; Galzio, Renato; Campero, Alvaro; Lawton, Michael T.; Luzzi, Sabino (Acta Biomedica Atenei Parmensis, 2022)
Introduction Intracranial aneurysms (IAs) are devastating cerebrovascular diseases with multifactorial etiology. The role of inflammation is indisputable, and interleukins are pivotal in supporting local inflammatory pathways and endothelial dysfunction at the aneurysm wall. In the light of insufficient evidence reported in the literature, this meta-analysis was aimed to investigate the genetic linkage between IL-1β (rs16944) -511C>T polymorphisms and IAs susceptibility. Methods A comprehensive online literature review was completed using the PubMed/Medline and Web of Science databases in accordance with the PRISMA guidelines. “Interleukin-1β,” “IL-1β,” “polymorphism,” “intracranial aneurysm,” and “subarachnoid hemorrhage” were the main keywords. Only human case-control studies, published from 2005 to 2021, written in English or translated, were screened. In the statistical analysis, we applied the fixed- and random-effect models, according to the level of heterogeneity, to assess the odds ratios (ORs) and 95% confidence intervals (CIs). RevMan 5.0 software was used for the statistics. Results Only 4 studies were eligible, with a total of 2070 patients, 1050 of which were assigned to the study group. Combined results showed a statistically significant association between the risk of IAs and -511CC (OR=0.79, 95% CI [0.65-0.95], p=0.01), and CT (OR=0.69, 95% CI [0.58-0.82], p<0.0001; OR=0.71, 95% CI [0.55-0.93], p=0.01) allele variations, both in the fixed- and random- models. No correlation was identified for the -511TT genotype (p=0.42; p=0.78). All the texts showed a low level of publication bias. Conclusion The present meta-analysis proved a potential role of IL-1β -511CC/CT genotypes in the pathogenesis of IAs. Additional studies are imperative to explain the underlying neuroimmune mechanisms, also allowing tailoring the potential inflammatory-target therapies for IAs.